(untitled) (Research, Society and Development, 2021)
Pregnancy is a very important and unique period in a woman’s life, since it is marked by physical and psychological changes that require care and monitoring by qualified professionals. Therefore, this study aims to describe the experience of nursing students in health education experiences with pregnant women based on Paulo Freire’s theoretical framework. This is a descriptive study with a qualitative approach carried out with pregnant women in the Family Health Center - FHC of the neighborhood Padre Palhano, Sobral - Ceará. During the educational interventions topics such as breastfeeding, pregnant women’s rights, urinary tract infection, parturition, normal delivery and cesarean section were addressed. The activities carried out in the Family Health Strategy are considered of fundamental importance, since they provided the construction of knowledge and exchange of knowledge, from a perspective of problematization and reflection, contributing to the care of pregnant women in the Unified Health System.